Hadith #3924 - Sunan Abi Dawud - al-Mufadl bin Fadala bin 'Ubaid المفضل بن فضالة بن عبيد بن ثمامة; Habib bin al-Shaheed al-Azdi حبيب بن الشهيد الأزدي; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Uthman bin Muhammad; Yonus bin Muhammad bin Muslim يونس بن محمد بن مسلم المؤدب (Sunan Abi Dawud)
A man said: Messenger of Allah! we were in an abode in which our numbers and our goods were many and changed to an abode in which our numbers and our goods became few. The Messenger of Allah (ﷺ) said: Leave it, for it is reprehensible.
Grade: Hasan

Hadith #4973 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib bin al-Shaheed al-Azdi حبيب بن الشهيد الأزدي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
To proceed (amma ba’d)
Grade: Sahih

Hadith #5227 - Sunan Abi Dawud - Habib bin al-Shaheed al-Azdi حبيب بن الشهيد الأزدي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Lahaaq bin Hameed bin Sa'id لاحق بن حميد بن سعيد أبو مجلز; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
In the pre-Islamic period we used to say: “May Allah make the eye happy for you,” and “Good morning” but when Islam came, we were forbidden to say that. AbdurRazzaq said on the authority of Ma’mar: It is disapproved that a man should say: “May Allah make the eye happy for you,” but there is no harm in saying: “May Allah make your eye happy.
Grade: Da'if